2021
DOI: 10.1002/pbc.29065
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1 study of prexasertib (LY2606368), a CHK1/2 inhibitor, in pediatric patients with recurrent or refractory solid tumors, including CNS tumors: A report from the Children's Oncology Group Pediatric Early Phase Clinical Trials Network (ADVL1515)

Abstract: Background: Prexasertib (LY2606368) is a novel, second-generation, selective dual inhibitor of checkpoint kinase proteins 1 (CHK1) and 2 (CHK2). We conducted a phase 1 trial of prexasertib to estimate the maximum-tolerated dose (MTD) and/or recommended phase 2 dose (RP2D), to define and describe the toxicities, and to characterize the pharmacokinetics (PK) of prexasertib in pediatric patients with recurrent or refractory solid and central nervous system (CNS) tumors. Methods: Prexasertib was administered intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 29 publications
(74 reference statements)
0
15
0
Order By: Relevance
“…By identifying new SMYD3 interactors involved in important cancer hallmarks, this study extends the range of potential pathways amenable to co-targeting with this approach. Indeed, several inhibitors of SMYD3 molecular partners are currently used in clinical practice or are being investigated in clinical trials; the most recent ones include temsirolimus, an mTOR inhibitor [113] ; capivasertib, an AKT inhibitor [114] ; tivantinib, a c-MET inhibitor [115] ; apatinib, a VGFR inhibitor [116] ; M4076, an ATM inhibitor [113] ; prexasertib, a CHK2 inhibitor [117] ; and onalespib, an HSP90 inhibitor [118] .…”
Section: Discussionmentioning
confidence: 99%
“…By identifying new SMYD3 interactors involved in important cancer hallmarks, this study extends the range of potential pathways amenable to co-targeting with this approach. Indeed, several inhibitors of SMYD3 molecular partners are currently used in clinical practice or are being investigated in clinical trials; the most recent ones include temsirolimus, an mTOR inhibitor [113] ; capivasertib, an AKT inhibitor [114] ; tivantinib, a c-MET inhibitor [115] ; apatinib, a VGFR inhibitor [116] ; M4076, an ATM inhibitor [113] ; prexasertib, a CHK2 inhibitor [117] ; and onalespib, an HSP90 inhibitor [118] .…”
Section: Discussionmentioning
confidence: 99%
“…There was a pediatric trial of the CHK1 inhibitor prexasertib, but no patients with neuroblastoma were enrolled (NCT02808650). 52 Because of the known alterations in checkpoint control, PARP inhibitors are also of clinical interest and in pediatric development.…”
Section: Targeting Genomic and Other Vulnerabilitiesmentioning
confidence: 99%
“…In a Phase II trial, MK-8776 tested as an adjunct to AraC (Cytarabine) treatment for relapsed acute myeloid leukemia also showed adverse effects on cardiac function and other organ toxicities but no clinical benefit beyond that of AraC alone (NCT01870596). LY2606368 (Prexasertib) is a Chk1i that causes mitotic catastrophe (also termed replication catastrophe) in vitro and showed antitumor activity in preclinical animal studies [ 164 ], yet in several Phase I/II trials, LY2606368 has shown limited clinical benefit with occasional serious side effects [ 120 , 121 , 122 , 123 ]. Wee1 is a checkpoint kinase in the ATR/Chk1/Wee1 pathway that negatively regulates the G2/M transition, among other functions [ 165 ].…”
Section: Targeting Replication Stress Signaling and Fork Repair/resta...mentioning
confidence: 99%